HUBUNGAN ANTARA KARAKTERISTIK IBU DENGAN STATUS GIZI BALITA DI DESA KLAHANG KECAMATAN SOKARAJA KABUPATEN BANYUMAS - Ulfah Agus Sukrillah; Herry Prasetyo; Meisye M Kuhu (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2012)
ABSTRACT There are several mother’s characteristic such as the level of education, knowledge, and the number of children in the family and the mother’s income is assumed with the relation of child under five nutrition status. This research constitutes quantitative study that employs descriptive correlation method words : 118 sample of respondent (92,9%) by using questionnaires and observation of child under five nutrition status through the measuring of the body weight to the age.The research result by using Rank Spearman analysis states there is a relation between the level mother’s education with the child under five nutrition status (rho –0,252 and p-value 0,006), there is no relation between the mother’s knowledge with the child under five nutrition status (rho –0,103 and p value 0,265), there is no relation between the number of children in the family with the child under five nutrition status (rho –0,087 and p value 0,349), and there is no relation between the mother’s income with the child under five nutrition status (rho 0,128 and p value 0,128). There are many of child under five in under nutrition status (16,9%), which need more attention from health public services to give more intensive information for the mother with the child under five in under nutrition about the important of nutrient for the child under five through the health public it self or home visit. Keywords : Mother’s characteristic, The child under five nutrition status Kesmasindo Volume 5, Nomor 2, Juli 2012, hlm. 121- 135